2008
DOI: 10.1590/s0103-64402008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term effect of COX-2 selective inhibitor as an adjunct for the treatment of periodontal disease: a clinical double-blind study in humans

Abstract: Adjunctive therapeutic strategies that modulate the inflammatory mediators can play a significant role in periodontal therapy. In this double-blind, placebo-controlled study, 60 subjects diagnosed as periodontitis patients were evaluated for 28 days after periodontal treatment combined with selective cyclooxygenase-2 (COX-2) inhibitor. The experimental group received scaling and root planning (SRP) combined with the Loxoprofen antiinflammatory drug (SRP+Loxoprofen). The control group received SRP combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…51,52 Adjunctive anti-inflammatory therapy may lead to a faster and greater reduction in probing pocket depth than conventional periodontal therapy. 53 So, the regular use of NSAIDs by SCD patients may result in prevention of periodontal destruction in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Adjunctive anti-inflammatory therapy may lead to a faster and greater reduction in probing pocket depth than conventional periodontal therapy. 53 So, the regular use of NSAIDs by SCD patients may result in prevention of periodontal destruction in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that COX-2 inhibitors were able to reduce the symptoms of periodontitis patients [97]. Nevertheless, COX-2 expression in inflamed gingival tissues from chronic periodontitis patients was lower and its promoter was hypermethylated [98], which was confirmed by an independent study [99].…”
Section: Epigenetics In Periodontitismentioning
confidence: 71%
“…Metronidazole affects specifically the anaerobic oral flora, including P. gingivalis, T. forsythia and T. denticola, microorganisms attached to the red Socransky's complex 50 , while A. actinomycetemcomitans, an optional anaerobic bacterium, appears to be widely opposed by the amoxicillin 38-39,41. The anti-inflammatory effect in the AP treatment was not observed. In addition, the studies with these drugs have inconsistent data and, therefore, do not allow any indication [46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study has demonstrated clinical benefit (PD reduction in deep pockets) when loxoprofen was associated with SRP in patients with periodontal disease, not being specified the subtype disease 47 .…”
Section: Anti-inflammatorymentioning
confidence: 99%